Thrombus heterogeneity in ischemic stroke. (3rd April 2021) - Staessens, Senna; De Meyer, Simon F.
Abstract: The structure of stroke thrombi has gained an increasing amount of interest in recent years. The advent of endovascular thrombectomy has offered the unique opportunity to provide and analyze thrombi removed from ischemic stroke patients. It has become clear that the composition of ischemic stroke thrombi is relatively heterogenous and various molecular and cellular patterns become apparent. Good understanding of the histopathologic characteristics of thrombi is important to lead future advancements in acute ischemic stroke treatment. In this review, we give a brief overview of the main stroke thrombus components that have been recently characterized in this rapidly evolving field. We also summarize how thrombus heterogeneity can affect stroke treatment.